2009
DOI: 10.1159/000189271
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Second-Line Therapies in Interferon-Beta-Treated Relapsing-Remitting Multiple Sclerosis Patients

Abstract: Background:Interferon-β (IFNB) therapies are the most widely used as first-line intervention in the treatment of relapsing-remitting (RR) multiple sclerosis (MS). Despite long-term experience, however, the definition and prediction of response remain controversial. Aim:The objective of this study was to assess the long-term validity of the main clinical definitions of response applied after 1 and 2 years of IFNB therapy in a cohort of RRMS patients followed up for at least 5 years. Methods:We tested these diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…reduced ARR, delayed disease progression) was observed in patients who converted from one DMT to another [5, 6, 14, 4043]. Our findings also emphasize the importance of changing a therapeutic regimen to improve patients’ well-being (i.e.…”
Section: Discussionsupporting
confidence: 56%
“…reduced ARR, delayed disease progression) was observed in patients who converted from one DMT to another [5, 6, 14, 4043]. Our findings also emphasize the importance of changing a therapeutic regimen to improve patients’ well-being (i.e.…”
Section: Discussionsupporting
confidence: 56%
“…On the whole, considering that 122 patients (35%) stopped treatment, this could limit the use of MMF in patients with MS. However, such a discontinuation rate of therapy is also observed with interferon b in patients with MS 19. Our results concerning safety are in agreement with data found in previous studies: in 2004, a study of 79 MS patients treated with MMF suggested a good safety profile with potential therapeutic effects 13.…”
Section: Discussionsupporting
confidence: 92%
“…First, it has proven difficult to validate definitions of treatment failure for clinical use; some factors for consideration are listed in Table 5. [114][115][116][117] Second, more work is needed to understand the types of short-term change that might predict longer-term prognosis. 118 Third, there are few head-to-head DMT trials or trials that assess specific DMTs as a next option specifically in the setting of failure of another DMT.…”
Section: Sequential Dmt Monotherapymentioning
confidence: 99%